การประเมินลักษณะประชากรงาขี้ม้อนพื้นเมืองจาก ภาคเหนือตอนบนของประเทศไทย - สิรภัทร บุญปั๋น (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Native species generally have high genetic diversity. These variations play an important role as genetic resources for plant breeding. Local perilla (Perilla frutescens (L.) Britt.), an endemic crop in Upper Northern Thailand, is expected to be genetically diverse. The objective of this study was to examine variation in morphological characteristics, yield potential and seed quality of 3 groups of local perilla varieties from 3 different locations, group 1:15 seed samples from Mae Hong Son); group 2: 12 seed samples from Chiang Mai and Lamphun and group 3: 12 seed samples from Chiang Rai, Nan, Phrae, Lampang and Phayao. The study consisted of two experiments. The first experiment was conducted at Department of Plant Science and Natural Resource, Faculty of Agriculture, Chiang Mai University. This experiment aimed to determine basic morphological characteristics of 39 perilla seed samples from farmers. From each seed sample 100 seed were examined for seed color and 1000 seeds weight were recorded in triplicates. From each seed sample 5 plants were grown in 5 plastic pots (the pot size was 30 cm-diameter, 35 cm-height)containing soil. When plants were 6-8 weeks old, color of the leaf surface, color of the leaf underside and color of stem were recorded. At 15-20 weeks when the plant reached fully vegetative stage before flowering leaf length and width, length of peduncle, shape of leaf and aroma of plant were recorded. Diversity of morphological character within and between populations was evaluated by using Shannon-Weaver index (H’) and descriptive statistics. Variation in seed color was found within and between farmers’ seed samples. Shannon-Weaver index (H’) ranged from 0.0701 to 0.5185. Mean 1000 seed weight of the samples ranged from 0.82 g to 2.03 g, Variation was found between populations in color of the leaf underside, color of stem, shape of leaf and aroma of the plant, while the leaf surface was all green. In the progeny test, quantitative variations between populations in leaf size (length x width) and length of leaf peduncle were found. The second experiment was conducted at Mae Hia Agricultural Research, Demonstrative and Training Center, Faculty of Agriculture, Chiang Mai University. The objective of this experiment was to evaluate 14morphologicaland agronomic characteristics, yield components and 4 characters of seed quality analysis in field grown perilla. The 39 seed samples as in experiment 1 were planted in plots were arranged in Randomized Complete Block Design (RCBD) with 3 replications in July 2011 and grown during rainy season. At flowering stage, color of leaf surface, color of the leaf underside, color of stem, degree of pubescence, color of flower and flowering date were recorded. At maturity and harvest stage, plant height, number of internodes, number of branches, length of the largest inflorescence, number of florets of the largest inflorescence and color of seed were record and yield/rai and 1000 seeds weight were determined. Diversity of morphological characteristic within and between populations was evaluated by using Shannon-Weaver index (H’). Mean, standard deviation (sd) and coefficient of variation (cv) were evaluated for variation of physiological characteristic within and between populations. Experiment analyzed crude fat and unsaturated fatty acid by random collected from seed harvested in field experiment. Crude fat was analyzed by soxhlet method and data analysis by Pathak et al. (1996). Investigation of type and content for unsaturated fatty acid were done by using Gas Chromatography (GC) technique. The 12 populations of most high Linolenic (Omega3) content from experiment 2.2 were selected for analyzed amount of vitamin E by High Performance Liquid Chromatography (HPLC) technique. Content of vitamin E was analyzed and compared by AOCS (Method Ce8-89) (AOCS, 1997). Variation was found within and between populations in seed color of the field grown perilla. Shannon-Weaver index (H’) were in range of 0.2867 – 0.5781. The variation was found between populations in degree of pubescence trait but not found in the other morphological traits. The quantitative variations consist of agronomic characteristic and yield components were found variation between populations all characteristic (i.e. flowering date, plant height, number of internodes, number of branches, length of the largest inflorescence, number of floret of the largest inflorescence, 1000 seeds weight and yield/rai), and crude fat ranged from 8.64% to 49.1%. Unsaturated fatty acid Linolenic acid (Omega3) ranged from 15.7% – 86.1 % of the total fatty acid, Linoleic acid (Omega6) 8.7 – 48.1 %and Oleic (Omega9) 3.3 – 18.7 %.15.7 – 86.1 %, Variation was also found of vitamin E type  - Tocopherol in crude fat among the selected samples. The most interesting population was collected from Ban Hong district, Lamphun province, because of highest vitamin E (612.9 µg/g dw) and Linolenic (Omega3) (86.1 %).